ELECTROCHEMICAL BEHAVIOR OF SILVER IN A SULPHURIC ACID SOLUTION - Baeshov Abduali Baeshovich,; Tuleshova Elmira Zhanbirbayevna,; Baeshova Azhar Kospanovna,; Ozler Mehmet Ali,; Aripzhan Gulnur Zhoiankyzy, (Academic Scientific Journal of Chemistry, 2020)
In recent years, alternating current has been widely used in various fields of chemical and electrochemical technology. When a symmetric alternating current passes through an electrochemical cell, in principle there should be no visible changes, since the product restored to the cathode half-period should be oxidized back to the anodic half-period. However, depending on the conditions of electrolysis, electrode material, etc. a purposeful course of the electrochemical process is possible. The paper shows the distinctive features of electrochemical processes occurring on a silver electrode during electrolysis by industrial alternating current in a solution of sulfuric acid by the method of rational mathematical planning. The optimal conditions for the dissolution of silver are determined by studying the effect of current density at the electrodes, the concentration and temperature of the electrolyte, the duration of the electrolysis and the frequency of the alternating current. It is shown that when polarized with an alternating current of silver in a pair with a titanium electrode, the process of passivation of the silver electrode is eliminated, and the rate of dissolution of the metal increases.